Naïve bayes algorithm for early diagnosis of non-communicable diseases - Ramadhan, Nuzul; Ramli, Rakhmat Kurniawan (Journal of Intelligent Decision Support System (IDSS), 2025)
Non-communicable diseases such as heart disease, diabetes mellitus, hypertension, stroke, asthma, rheumatism, and GRED are still the main causes of illness and death in Indonesia. This problem is more serious in rural areas with limited health services, such as Lubuk Palas Village, Asahan Regency, which faces obstacles in distance, road infrastructure, and a limited number of medical personnel, so early diagnosis is often neglected. This research aims to apply the Naïve Bayes method in a non-communicable disease diagnosis expert system and develop web and mobile-based applications to support the community and medical personnel in early detection. The research method combines primary data from observations and interviews with health workers and secondary data from medical literature. Each symptom is given a probability weight of 0.00–1.00 according to medical consultation, then processed using the Naïve Bayes algorithm with two approaches, namely direct calculation and gradual filtering. The results show that the system produces a posterior probability of 99.32% in the heart disease scenario with typical symptoms and 90.00% in the stroke scenario with partial symptoms. The findings of this research are that the application of two Naïve Bayes inference pathways is proven effective in producing an initial diagnosis that is adaptive to variations in symptoms, relevant for rural conditions with limited health services, and capable of providing fast, practical, and widely accessible medical decision support.